Analisis Perbedaan Persepsi Auditor Eksternal dan Pemakai Jasa terhadap Kepatuhan Akuntan Publik - Ardini, Lilis (Jurnal Widya Manajemen & Akuntansi, 2005)
The objective of this study was finding out the complience perception level of public accountant by involving external auditor and user as responder and observing wheter there are differences among each group or not.